Ipoh the untold story - Berbar, Henry; Lim, Poh Sze (Amos HBL Ventures Sdn Bhd, 2019)
A land with striking duality, this federation of 14 states is anchored on industrialism, economic and cultural modernity as well as its traditionalism where the second largest state in Peninsular Malaysia is the state of Perak, meaning silver in Malay, arouses much curiosity. If there is one place worthy of a visit in West Malaysia, it would be the city of Ipoh. '